Problematika Nikah Hamil di Kantor Urusan Agama (KUA) Studi Kasus KUA Rappocini - Shalihah, Nurul Imraatu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Marriage while pregnant is a phenomenon that occurs quite frequently in society and causes various problems, especially in the administrative process at the Office of Religious Affairs (KUA). This study aims to analyze the problems faced by the Rappocini District KUA in handling the marriage of pregnant couples before the marriage ceremony as well as the legal views underlying it. This research uses a qualitative approach with a case study method through interviews with the head of the KUA and penghulu, as well as a review of applicable regulations. The research results show that there are various obstacles in carrying out marriages while pregnant, both from legal, social and administrative aspects at the KUA.